2017
DOI: 10.1016/j.brachy.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Pulse sequence considerations for simulation and postimplant dosimetry of prostate brachytherapy

Abstract: High-resolution, high-contrast images help facilitate target delineation and provide accurate localization of the radioactive seeds in the simulation and post-implant dosimetry of prostate brachytherapy. Magnetic resonance imaging (MRI) offers many potential advantages for this application over the current standard of practice of computed tomography (CT). However, MRI is technically complex and has many more user-selectable scan parameters, which can impact image quality, than does CT. In this paper, we provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Imaging both the seed markers and anatomy previously required co‐registration of multiple MR images with different contrasts . Researchers recently demonstrated that the seed markers and anatomical structures could be imaged in a single acquisition using a balanced SSFP pulse sequence and an endorectal coil (ERC) . Although balanced SSFP imaging provides an accurate means for seed localization, certified medical dosimetrists (CMDs) must manually identify each seed in the MR images, which is time consuming and may require co‐registration or cross‐referencing with a post‐implant CT acquisition to identify inconspicuous seeds near anatomic boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging both the seed markers and anatomy previously required co‐registration of multiple MR images with different contrasts . Researchers recently demonstrated that the seed markers and anatomical structures could be imaged in a single acquisition using a balanced SSFP pulse sequence and an endorectal coil (ERC) . Although balanced SSFP imaging provides an accurate means for seed localization, certified medical dosimetrists (CMDs) must manually identify each seed in the MR images, which is time consuming and may require co‐registration or cross‐referencing with a post‐implant CT acquisition to identify inconspicuous seeds near anatomic boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that such a high rBW will result in substantial loss of SNR (approximately 30% or more). Therefore, increases in the number of signal averages, use of phase and slice oversampling, or reduction in parallel imaging acceleration factors may be required to recover SNR 81,82 . Each of these changes will increase the scan times.…”
Section: Clinical Implementation Of Mri For Hdr Btmentioning
confidence: 99%
“…Other sequences have also been utilized for improved reconstruction of the applicator and/or detection of seeds or markers. These include 3D T1 weighted (T1W) gradient echo sequences such as VIBE or LAVA, 56,82 or 3D phase cycled steady-state free precession sequences such as CISS, FIESTA-C, or balanced FFE. 82,84 These sequences are generally fast compared with 3D FSE VFL sequences but produce less desirable contrast of the anatomy and lesion unless used with contrast agents.…”
Section: Gyn Bt (Institutionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we would plan to maintain the existing didactic sessions, which could be presented in-person or alternatively as prerecorded or virtual lectures. For the simulation portion, we would add MRI-based preplanning, which is a critical component for MRI-assisted radiosurgery quality assessment (12,33,34). We would also recommend a formal evaluation of procedural competency using a standardized checklist of the technical steps that could be filled out by the observing faculty, similar to metrics used by our colleagues in GYN and breast brachytherapy simulation (23,35).…”
Section: Discussionmentioning
confidence: 99%